Chemical Composition of Essential Oils from Six Zanthoxylum Species and Their Repellent Activities against Two Stored-Product Insects. (28th August 2017) - Zhang, Wen-Juan; Zhang, Zhe; Chen, Zhen-Yang; Liang, Jun-Yu; Geng, Zhu-Feng; Guo, Shan-Shan; Du, Shu-Shan; Deng, Zhi-Wei
Abstract : The objective of this study was to analyze six essential oils from Zanthoxylum genus (family Rutaceae) in China and evaluate their repellent activities against Tribolium castaneum and Lasioderma serricorne adults. Six essential oils from Zanthoxylum genus, including Z. armatum, Z. dimorphophyllum, Z. dimorphophyllum var. spinifolium, Z. piasezkii, Z. stenophyllum, and Z. dissitum, were obtained by hydrodistillation and their yields were ranging from 0.02% to 0.53%. Totally, there were 39 chemical components revealed by GC-MS. Among them, some components with high relative content existed in more than three Zanthoxylum species. For instance, both δ -cadinene (1.21%–17.15%) and spathulenol (0.36%–10.19%) appeared in essential oils of Z. dimorphophyllum, Z. piasezkii, Z. stenophyllum, and Z. dissitum which were found to have higher content of sesquiterpenoids. The repellent activities of six essential oil samples against T. castaneum and L. serricorne adults were investigated for the first time. Data demonstrated that six Zanthoxylum species had much stronger repellent activities against T. castaneum than L. serricorne adults, especially in 2 hours after exposure. The results indicate that these six essential oils from Zanthoxylum have significant potential to be developed into natural repellents to control insects in grains, food, and traditional Chinese medicinal materials.